2020
DOI: 10.3892/etm.2020.9531
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of APRI and FIB‑4 in HCV cirrhotic patients who achieved SVR after DAA therapy

Abstract: There are limited data available on the regression of fibrosis in hepatitis C virus (HCV) patients who have achieved sustained virologic response (SVR) after interferon-free treatments. Moreover, a perfect method for assessing liver fibrosis and its dynamics has not been established yet. The main objective of this study was to evaluate the dynamics of aspartate aminotransferase to platelet ratio index (APRI) and Fibrosis-4 (FIB-4) scores in patients with HCV who registered SVR. We performed ROC curve analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There are limited data available on the dynamic changes in liver stiffness among patients with cirrhosis who achieved SVR after interferon-free treatment. However, a significant decrease in the values of APRI and FIB-4 was observed among 164 patients with cirrhosis who achieved SVR with DAA [28]. The German Hepatitis C-Registry [29] found that patients with cirrhosis had a higher magnitude of transient elastography improvement between the baseline and follow-up (25.1 kPa vs. 21.5 kPa; p = 0.002) than those with F2-F3 (8.9 kPa vs. 8.8 kPa; p = 0.060) or F0-F1 (5.3 kPa vs. 5.2 kPa; p = 0.064).…”
Section: Discussionmentioning
confidence: 96%
“…There are limited data available on the dynamic changes in liver stiffness among patients with cirrhosis who achieved SVR after interferon-free treatment. However, a significant decrease in the values of APRI and FIB-4 was observed among 164 patients with cirrhosis who achieved SVR with DAA [28]. The German Hepatitis C-Registry [29] found that patients with cirrhosis had a higher magnitude of transient elastography improvement between the baseline and follow-up (25.1 kPa vs. 21.5 kPa; p = 0.002) than those with F2-F3 (8.9 kPa vs. 8.8 kPa; p = 0.060) or F0-F1 (5.3 kPa vs. 5.2 kPa; p = 0.064).…”
Section: Discussionmentioning
confidence: 96%
“…Chitinase‐3‐like protein 1 (CHI3L1), is a highly liver‐enriched protein and a driving force of liver fibrosis, serves as a novel noninvasive liver fibrosis biomarker that can accurately stages different stages of liver fibrosis [ 14 ] according to the Metavir Fibrosis Stage [ 11 ] (F0–F4) classification. The aspartate aminotransferase (AST)‐to‐platelet ratio (APRI) and fibrosis‐4 (FIB‐4), two commonly used fibrosis indicators, [ 15 ] along with CHI3L1 [ 16 , 17 ] were used to evaluate liver fibrosis.…”
Section: Methodsmentioning
confidence: 99%
“…The study outcome was the presence of severe liver fibrosis – defined as an FIB-4 >3.25 – as a binary time-varying variable. 14 The choice to use the FIB-4 index was based on its capacity to accurately predict advanced stages of liver fibrosis even after HCV cure, 15 , 16 and its ability to predict complications such as hepatic decompensation and HCC in HCV-infected patients. 17 …”
Section: Methodsmentioning
confidence: 99%